Abnormal Contour Huge Uterine Fibroids - Ahmed, Parveen; Farid, GM; Ishague, Tanveen; Siddiqua, Ayesha (Medicine Today, 2016)
Uterine fibroids represent the most common large solid benign tumor of the female genital tract. This 35 years old lady, mother of one child represented to our clinic with a history of progressive abdominal swelling that had rapidly increased in the last two years. There were associated abdominal pain, easy fatigability, heavy menstrual loss and prolong secondary subfertility of about ten years. On examination abdomen was enlarged and the mass measuring about 25cm from xiphisternum, firm, irregular and fairly mobile. Pelvic ultrasound scan revealed features of huge multiple uterine fibroids and the size of the largest one was about 20x25cm,moderate bilateral hydro-nephrosis. Intraoperative findings were moderate pelvic adhesions, huge multiple fibroids and the largest measuring about 18x20cm. Total abdominal hysterectomy with preservation of both ovaries were done. Histopathological report confirmed benign leiomyoma with no evidence of malignancy. Medicine Today 2015 Vol.27(2): 49-50